Accessing communication: The quality of live subtitles in the UK. (July 2016) - Romero-Fresco, Pablo
Abstract: This article presents the results of the first official assessment on the quality of live TV subtitles in the UK as a form of access to audiovisual communication for deaf and hard-of-hearing viewers. Carried out in collaboration with the British governmental regulator Ofcom, this is the largest analysis ever conducted on the quality of live subtitles, covering 300 programmes and 78, 000 subtitles. The results provide data on the key issues of accuracy, speed, reduction rate and latency of the subtitles. The article concludes with a number of suggestions to update the existing guidelines on live subtitles at an international level so that they can provide full access to audiovisual communication for viewers with hearing loss. Highlights: Subtitling is a key form of access to audiovisual communication for deaf viewers. This article presents the largest study conducted so far on live subtitling quality. Live subtitles in the UK meet the accuracy target but their delay is too high. National and international guidelines should be revised to be in line with results.